2003
DOI: 10.1080/1025389031000111302
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Cardiovascular and Hypothalamic-Pituitary-Adrenal Axis Responses to Psychological Stress in Healthy Older Adult Men and Women

Abstract: Gender differences in the neuroendocrine and cardiovascular response to psychological stress may contribute to the gender differences in the prevalence of diseases associated with hypothalamic-pituitary-adrenal (HPA) axis reactivity such as cardiovascular disease (CVD), diabetes and hypertension. We measured plasma ACTH, cortisol, heart rate (HR), and blood pressure (BP) responses in 8 men and 8 women (55-75 years) exposed to the Matt Stress Reactivity Protocol (MSRP), a psychological challenge. The MSRP elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 30 publications
4
63
0
2
Order By: Relevance
“…Although there is substantial evidence for such a sexual differentiation in HPA sensitivity in rats (Kitay, 1961;Critchlow et al, 1963;Le Mevel et al, 1979;Seale et al, 2004), this distinction is less clear in humans. Indeed, certain studies suggest that HPA drive is greater in males compared to females under certain conditions (Kirschbaum et al, 1999;Kudielka et al, 1998;Seeman et al, 2001;Traustadottir et al, 2003). The present findings demonstrate sex differences in another system that is engaged by stress, the brain norepinephrine system, which modulates cognitive aspects of the stress response.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Although there is substantial evidence for such a sexual differentiation in HPA sensitivity in rats (Kitay, 1961;Critchlow et al, 1963;Le Mevel et al, 1979;Seale et al, 2004), this distinction is less clear in humans. Indeed, certain studies suggest that HPA drive is greater in males compared to females under certain conditions (Kirschbaum et al, 1999;Kudielka et al, 1998;Seeman et al, 2001;Traustadottir et al, 2003). The present findings demonstrate sex differences in another system that is engaged by stress, the brain norepinephrine system, which modulates cognitive aspects of the stress response.…”
Section: Discussionsupporting
confidence: 49%
“…There are demonstrations of an enhancement of the HPA response to stress or CRF in females (Gallucci et al, 1993;Jezova et al, 1996;Stroud et al, 2002) and estrogen-mediated increases in cortisol response in males (Kirschbaum et al, 1996). However, there are also reports of increased HPA responsivity in males (Kudielka et al, 1998;Kirschbaum et al, 1999;Traustadottir et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This adrenal sexual dimorphism is thought to be an important factor in explaining sex differences in relation to prevalent diseases associated with hypothalamic-pituitary-adrenal axis reactivity, such as cardiovascular disease, inflammation, diabetes, and hypertension (19,55). On the other hand, it has been suggested that a transient increase in ornithine decarboxylase (ODC) activity and tissue polyamines, termed the polyamine stress response, may be considered as an integral component of the cellular stress program (18), and, in consequence, sex-dependent differences in the ODC/polyamine system in the adrenals could be, in part, responsible for the sex dependence of the stress response.Polyamines are small aliphatic cations that are essential for the growth, differentiation, and function of normal cells (22,36,47,55,58). The cellular polyamine content is precisely regulated by multiple pathways that include transport mechanisms and biosynthesis from amino acid precursors.…”
mentioning
confidence: 99%
“…In the rat there is a marked sexual dimorphism in adrenal weight, plasma ACTH, and corticosterone concentrations, with females having higher values than males (1,25,27,30,45). This adrenal sexual dimorphism is thought to be an important factor in explaining sex differences in relation to prevalent diseases associated with hypothalamic-pituitary-adrenal axis reactivity, such as cardiovascular disease, inflammation, diabetes, and hypertension (19,55). On the other hand, it has been suggested that a transient increase in ornithine decarboxylase (ODC) activity and tissue polyamines, termed the polyamine stress response, may be considered as an integral component of the cellular stress program (18), and, in consequence, sex-dependent differences in the ODC/polyamine system in the adrenals could be, in part, responsible for the sex dependence of the stress response.…”
mentioning
confidence: 99%
See 1 more Smart Citation